2005
DOI: 10.1152/ajpregu.00781.2004
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived adrenomedullin controls blood volume through the regulation of arginine vasopressin production and release

Abstract: tral nervous system-derived adrenomedullin (AM) has been shown to be a physiological regulator of thirst. Administration of AM into the lateral ventricle of the brain attenuated water intake, whereas a decrease in endogenous AM, induced by an AM-specific ribozyme, led to exaggerated water intake. We hypothesized that central AM may control fluid homeostasis, in part by regulating plasma arginine vasopressin (AVP) levels. To test this hypothesis, AM or a ribozyme specific to AM was administered intracerebrovent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 52 publications
4
20
2
Order By: Relevance
“…While AVP is well known to control fluid balance by its antidiuretic action, OT, particularly when acting as a neurotransmitter, has been implicated as an important regulator of sodium balance (Balment et al 1980, Van Tol et al 1987, Blackburn et al 1992a,b, 1993, Verbalis et al 1995, Amico et al 2001, Fitts et al 2003, Rigatto et al 2003. We have previously demonstrated that brain-derived AM is a physiologic regulator of AVP secretion (Taylor et al 2005). i.c.v.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…While AVP is well known to control fluid balance by its antidiuretic action, OT, particularly when acting as a neurotransmitter, has been implicated as an important regulator of sodium balance (Balment et al 1980, Van Tol et al 1987, Blackburn et al 1992a,b, 1993, Verbalis et al 1995, Amico et al 2001, Fitts et al 2003, Rigatto et al 2003. We have previously demonstrated that brain-derived AM is a physiologic regulator of AVP secretion (Taylor et al 2005). i.c.v.…”
Section: Introductionmentioning
confidence: 86%
“…Two treatment groups were employed: one treated with the control scrambled ribozyme (2 mg in 2 ml saline) and another administered the AM-specific ribozyme (2 mg in 2 ml saline; Taylor & Samson 2002). Eighteen hours following ribozyme administration, when hypothalamic AM protein levels were decreased by w30% (Taylor & Samson 2002), rats were killed by decapitation and trunk blood was collected as before (Taylor et al 2005). Because decreased plasma levels of OT were predicted following central AM ribozyme treatment, OT levels were elevated in rats by i.p.…”
Section: Oxytocinmentioning
confidence: 99%
See 3 more Smart Citations